Revealing Orbital Tumors: A 2-Year Evaluation in Clinical Profile, Histopathological Features and Surgical Technique: Oral Presentation - Observational Study - Resident - Silmi Lisani Rahmani (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Incidence of orbital tumors is relatively low, but the delay in diagnosis, even if benign, can lead to vision loss and deformity. This study aims to review clinical and demographic information of orbital tumors in Sardjito General Hospital, Yogyakarta. Methods : We retrospectively reviewed clinical data of 138 patients who diagnosed with orbital tumors during July 2021 - March 2023. Data extracted included clinical characteristics, operative procedures, and histopathologic characteristics of orbital tumors. Results : There were 138 orbital tumors managed at hospital during a 2-year period. Among 138 patients, 82 patients (59%) were female and 56 patients (40%) were male. Twenty-one patients (15%) were in childhood age and 117 patients (84.8%) were in adulthood age. The common clinical manifestations were proptosis (83.3%) and decreased vision (10.4%). The main procedure used was anterior orbitotomy (54.34%). Eighty-eight patients (63.7%) have primary tumors and 51.4% of the orbital tumors were malignant. The most common orbital tumor in childhood age was a cyst (15%). On the other hand, in adult patients, the most common orbital tumor was meningioma (18%) and Non- Hodgkin Lymphoma (15.7%). There was an overall 8% complication rate after orbitotomy tumor removal, including decrease in vision (3.3%), ptosis (2.6%), and strabismus (1.3%). Conclusion : Orbital tumors are challenging group of tumors with proptosis become the most frequent clinical characteristic that found. The orbital tumors in childhood and adulthood differ significantly in their incidence and tumor type with the percentage of malignant tumors increasing with age.